2021
DOI: 10.7196/samj.2021.v111i3.15525
|View full text |Cite
|
Sign up to set email alerts
|

Blood shortage in COVID-19: A crisis within a crisis

Abstract: Blood shortage in COVID-19: A crisis within a crisis To the Editor: The coronavirus pandemic has had a devastating impact on healthcare resources in South Africa (SA) and the world at large. [1] Donor blood supplies are not exempt, with national blood banks reporting critical depletions. This is a chronic, multifaceted issue that SA has had to face long before the onset of the pandemic, as fewer than 1% of citizens are active blood donors. [2] Concerns had already been expressed by the South African National B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As there was none to minimal information on the transfusion requirement of COVID-19 patients, apprehension with regards to changes in the haematological profile, risk profile of COVID-19 patients and reduced number of blood donors, could have led to most doctors (71.8%) believing that shortage of blood components could also affect the transfusion management of COVID-19 patients [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As there was none to minimal information on the transfusion requirement of COVID-19 patients, apprehension with regards to changes in the haematological profile, risk profile of COVID-19 patients and reduced number of blood donors, could have led to most doctors (71.8%) believing that shortage of blood components could also affect the transfusion management of COVID-19 patients [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood shortages occurred during the COVID-19 pandemic. 2,3 Blood centers struggled to provide sufficient blood products to their clients promptly and hospital transfusion services struggled to decide how to allocate scarce resources to maximize patient benefit and minimize patient harm. Healthcare workers experienced significant stress from not knowing how to handle the unprecedented extreme shortages caused by multiple factors acting simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The blood supply depends on the availability of donors, blood center collection staff, blood donation supplies, reagents, and instruments. Blood shortages occurred during the COVID‐19 pandemic 2,3 . Blood centers struggled to provide sufficient blood products to their clients promptly and hospital transfusion services struggled to decide how to allocate scarce resources to maximize patient benefit and minimize patient harm.…”
Section: Introductionmentioning
confidence: 99%
“…While these approaches are used both in endemic and non-endemic countries, there is some evidence that in times of emerging pathogen outbreaks, laboratory tests may not be commercially available, require time to be implemented, and implementation may not be practical in outbreak areas or feasible in resource-constrained environments. The most recent experience with SARS-CoV-2 emergence has shown that, although SARS-CoV-2 may not be transfusion-transmitted, blood continuity can be adversely affected during pandemics [15,16].…”
Section: Introductionmentioning
confidence: 99%